Security Mechanisms For The Ipv4 To Ipv6 Transition. - Hj Mat Taib, Abidah; Budiarto, Rahmat (2007)

(untitled)
Transition from lpv4 to lpv6 has been made possible through various transition mechanisms, categorized as dual-stack tunneling and translation. However, period of transition may take years to complete which both protocols will coexist due to Internet services deployed are widely in lpv4.